Pollution prevention in wastewater networks: development of a biological early warning device - Black, Gary (Cranfield University, 2016)
A biological early warning system (EWS) was developed to screen wastewater containing nitrification inhibitors and identify nitrifying bacteria activity reduction without relying on absolute values of sensor signals. To do so, numerous sensors were evaluated using a tiered approach to aid the analysis and made it easier to convey the current state of the technology. The research then produced a framework for the development of an EWS and the applicability of sensors to the wastewater matrix. The research identified a need for the development of a strategy and guidance that can help in the prevention and detection of nitrification inhibitors. Initial tests focussed on sewer biofilm N2O emissions, however, despite average nitrification rates of 19.5 g-NH4 + - N.m- 2 .d- 1 the response was unreliable due to inadequate control. To address this, a circulating floating bed biofilm reactor (CFBBR) was designed as a sidestream. The CFBBR biofilm’s toxicity response was compared to the sewer biofilm, a 2850 mg.L- 1 MLSS culture and a 10.5 mg.L- 1 MLSS culture (with equivalent biomass concentration to the CFBBR biofilm). The cultures responded differently with an inhibitory effect scale of Cu2+ > ATU > Ni2+ > Cr6+ for CFBBR biofilm, ATU > Cu2+ > Ni2+ > Cr6+ for 2850 mg L- 1 MLSS, ATU > Ni2+ > Cr6+ > Cu2+ for 10.5 mg.L- 1 MLSS and ATU > Cu2+ > Cr6+ > Ni2+ for sewer biofilm. This was firstly attributed to suspended growth nitrification stimulation by Cu2+ doses up to ~45 mg.L- 1 resulting in a lower inhibitory effect. Secondly, very high Cr6+ and Ni2+ doses were required for biofilm nitrification inhibition, due to diffusion limitations and slow transport through cell membranes. The CFBBR biofilm response to heavy metals was characterised through N2O and CO2 spikes and a post shock emissions recovery period was observed with the trend Ni2+ > Cr6+ > Cu2+ . A 10 minute hydraulic retention time allowed quick detection and steady state nitrification rates of 0.4 g-NH4 + -N.m- 2 .d- 1 despite high organic loading rates. Additionally, a suspended growth based monitor (Nitritox) was assessed as an inlet works toxicity detector. Incorporation of a Nitritox with a CFBBR based sewer monitor offered increased robustness over a CFBBR only system and was shown to be viable system in catchments >200,000 population equivalent. This information is useful to water utilities so that they can plan for and experiment with upset early warning protocols. It is also useful to manufacturers as they can determine product performance needs.